2020
DOI: 10.1186/s12891-020-03442-8
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences of the journey to chronic widespread pain: a qualitative study

Abstract: Background: Chronic widespread pain (CWP) is a musculoskeletal disorder that affects approximately 10% of the population. It is more common in women than in men. It is important to understand how CWP develops and how it is maintained in order to prevent poor pain prognosis. Long term studies have shown that a mere part improves over time or fluctuates in their CWP condition. Female gender is one of the factors associated with persistence of CWP, suggesting men and women may experience their journey to CWP diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous research has found that work–life imbalance is the main factor in lower perceived health among individuals on, or at risk of going on, sick leave [ 53 ]. Moreover, women with CWP have described how unmanageable work-related demands had a negative impact on the pain [ 54 ]. Having too much work strain or feeling pressured to work more than their pain allowed aggravated the pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that work–life imbalance is the main factor in lower perceived health among individuals on, or at risk of going on, sick leave [ 53 ]. Moreover, women with CWP have described how unmanageable work-related demands had a negative impact on the pain [ 54 ]. Having too much work strain or feeling pressured to work more than their pain allowed aggravated the pain.…”
Section: Discussionmentioning
confidence: 99%
“…Safeguarding healthy relationships was experienced as essential to managing life stressors and balancing everyday life, including family, peers, and the relationship with oneself. A qualitative study exploring women’s experiences of CWP found that lack of social support had a negative impact and triggering effects on CWP [ 54 ]. Triggering factors included the experience of distrust, not being understood and social norms expectations, such as feelings of having to oblige everyone else, at the expense of oneself.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial risk factors include psychological suffering, insufficient social support, and limited decision-making authority (Keyaerts et al, 2022). Social factors include culture, beliefs, and cultural beliefs Keyaerts (2022), and individual characteristics consist of things like body mass index, age, gender, lifestyle, and living environment (Svensson et al, 2020). Given the influence of various risk factors on the incidence of MSDs, the implementation of prevention and control programs and measures requires the simultaneous identification and control of a series of risk factors (Tang et al, 2022) Some studies explain that Age, Length of work, Length of work, Gender, Workload, Repetition, Psychosocial factors, Work posture, Work climate, Stress, Body mass Index, Exercise frequency, History of muscle complaints, Education Anxiety, Fear, charity, company size, duration of work can be a risk factor for occurrence Muscoloskelatal Disorders (MSDs) (Shobur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%